Evaluation of Mortality Risk Factors of COVID-19 in Jakarta Tertiary Hospital During Peak of Second Wave and Predictive Utility of Community RT-PCR Low CT Values - Putra, Andika Chandra; Burhan, Erlina; Aufa, Akhdan; Bur, Rika; Pangestu, Hendri; Bahri, Syukrini; Souvriyanti, Elsye; Muchtiar, Mulyadi; Erlina, Andi; Aditama, Tjandra Yoga; Yuliwulandari, Rika; Kusuma, Indra; Suciati, Yulia; Rifqatussaadah, Rifqatussaadah; Jalal, Fasli; Gusnanto, Arief; Utomo, Ahmad Rusdan H (Indonesian Society of Respirology (ISR), 2024)
Background: The Delta variant of SARS-CoV-2 led to a surge in COVID-19 cases in Indonesia. This study aimed to assess the demographic profile and mortality rates of hospitalized COVID-19 patients in YARSI referral hospital, Jakarta, comparing pre-Delta and Delta wave periods. The study also investigated whether low CT values in RT-PCR tests indicated heightened viral transmission before the Delta wave surge. Method: A retrospective analysis was conducted on 1,457 COVID-19 patients hospitalized at YARSI (January-August 2021) and 25,279 RT-PCR test results from walk-in patients (April-August 17, 2021). Differences were evaluated using Chi-square or Fisher’s Exact Tests while binary logistic regression was used to assess mortality risk factors. Results: There were increased proportions of pregnant women, patients aged 20-29 and those with coronary artery disease during the Delta wave. This period also showed a significant increase in mortality rates, with the highest seen in patients >60 years old or those with multiple comorbidities. Notably, most of the deceased patients (131 of 139) were unvaccinated. Analysis of RT-PCR data showed rising percentages of positive results with low CT values (below 21 or 15) from April to June. Conclusion: The Delta wave saw a higher risk of hospitalization among young individuals and pregnant women, despite their low mortality risk. The unvaccinated and those with multiple comorbidities faced higher mortality risks. Increases in RT-PCR positivity with low CT values preceded the July COVID-19 case surge.